ird1 is a Vps15 homologue important for antibacterial immune responses in Drosophila. - Wu, J.; Randle, K.E.; Wu, L.P. (Cellular Microbiology, 2007)
The immune response-deficient 1 (ird1) gene was identified in a forward genetic screen as a novel regulator for the activation of Imd NFkappaB immune signalling pathway in Drosophila. ird1 animals are also more susceptible to Escherichia coli and Micrococcus luteus bacterial infection. ird1 encodes the Drosophila homologue of the Vps15/p150 serine/threonine kinase that regulates a class III phosphoinositide 3-kinase and is necessary for phagosome maturation and starvation-induced autophagy in yeast and mammalian cells. To gain insight into the role of ird1 in the immune response, we examine how amino acid starvation affects the immune signalling pathways in Drosophila. Starvation, in the absence of infection, leads to expression of antimicrobial peptide (AMP) genes and this response is dependent on ird1 and the Imd immune signalling pathway. Starvation, in addition to bacterial infection, suppresses the AMP response in wild-type animals and reduces the ability to survive M. luteus infection. Our results suggest that starvation and innate immune signalling may be intimately linked processes.